Premature pubarche, hyperinsulinemia, hypothyroxinemia and hyperintensities in basal ganglia: All caused by a single congenital defect - (:unkn) unknown (Galenos Yayincilik,, 2016)
Objective: Premature pubarche is the occurrence of pubic hair <8 years of age in girls and is mostly idiopathic but can be due to various virilising conditions such as congenital adrenal hyperplasia and androgen secreting tumours. To present two cases with premature pubarche and associated endocrine problems which have not been described previously. Case: Two girls, presented 10 years apart with the same complaint of early pubarche at age 7 years, with inappropriately low dehydroepiandrosterone sulfate levels. In addition to hyperandrogenemia (elevated testosterone and androstenedione) and advanced bone age, both had hyperinsulinemia, hypothyroxinemia, and hyperintensities in basal ganglia. The 2nd case also had symptomatic hypoglycemia. Investigations revealed a common congenital defect explaining all these manifestations. Conclusion: Pathogenetic mechanisms leading to all these manifestations will be discussed. © 2016, Galenos Yayincilik. All Rights Reserved.